Prevalence and sociodemographic characteristics of parents among patients treated in adult psychiatric hospitals – a register-based nationwide study - Heuckendorff, Signe; Brund, Rene B. K.; Buhl-Wiggers, Julie; Thorup, Anne A. E.; Ranning, Anne; Müller, Anne Dorothee; Fonager, Kirsten (Frontiers in Psychiatry, 2025)
IntroductionChildren of parents with mental illness face heightened risks of adverse health, social, and educational outcomes. Yet, families affected by parental mental illness are often overlooked in mental health and social care systems. Identifying parents in psychiatric care enables targeted interventions to mitigate intergenerational risks. This study aims to estimate the prevalence and describe the sociodemographic characteristics of patients in psychiatric hospital services in Denmark who are parents, with particular focus on those living with minor children, to inform future preventive support strategies.MethodsUsing Danish nationwide register data from 2020-2022, we identified individuals with at least one adult psychiatric hospital contact. Parenthood was determined through linkage to the Civil Registration System, including children aged 0–29 years. Diagnoses, socioeconomic status, and living arrangements were described, and associations between parental characteristics and co-residence with a minor child were described using crude relative risks.ResultsAmong 164,223 patients in psychiatric hospital services, 24% had at least one minor child (aged 0–17 years), and 8% had only adult children (aged 18–29 years). The most common diagnoses among parents with minor children were neurotic and stress-related disorders (31%) and affective disorders (25%). Geographic and diagnostic variation in the prevalence of parents was observed, and parent patients generally had higher socioeconomic status than non-parent patients. Among parent patients, those with a partner, higher education, and labor market affiliation were more likely to live with their child.ConclusionsOne in four Danish psychiatric hospital patients have minor children, highlighting the need for systematic identification and tailored services. The findings underscore the importance of integrating family-focused approaches within psychiatric care to reduce the long-term burden on children and break cycles of mental illness.